2002
DOI: 10.1093/rheumatology/41.4.381
|View full text |Cite
|
Sign up to set email alerts
|

The wafer test: a semi-quantitative test to screen for xerostomia

Abstract: The wafer test is valid and reliable for identifying subjects with xerostomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…The remaining 11 studies [4,32,35,38-42,45-47] described different methods for determining salivary hypofunction.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 11 studies [4,32,35,38-42,45-47] described different methods for determining salivary hypofunction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies that have shown patient-derived data tend to reflect the actual amount of saliva (29,32); however, it is accepted that potential differences can occur between what the patient reports and the actual measurement of saliva flow. It would not be feasible to measure saliva flow objectivity in every clinic, but a relatively simple measure is the time taken for the dissolution of a wafer (33). This could be included in further studies exploring xerostomia severity and the cutoff of the UW-QOL saliva domain in triggering intervention.…”
Section: Discussionmentioning
confidence: 99%
“…26 Like scintigraphy, the wafer test is a semiquantitative functional analysis method, employed in the initial diagnosis of salivary gland disorders. 27 Magnetic resonance (MR) provides excellent image contrast for soft tissues and spatial definition, with the advantage of not using ionizing radiation. 28 In sialography by MR, the saliva itself serves as contrast in obtaining the images.…”
Section: Diagnosis Of Salivary Dysfunctionsmentioning
confidence: 99%